Principaux traits socio-économiques de la région Saguenay - Lac-Saint-Jean - Pépin, Pierre-Yves (Cahiers de géographie du Québec, 1962)
The Saguenay - Lake Saint-Jean region was only settled during the past one hundred years but now contains a population of approximately 260,000 (1961). This rapid growth of population is explained in great measure by an exceptionally high rate of natural increase. Much urbanisation bas recently occurred, particularly in the upper Saguenay area where the conurbation consisting of Chicoutimi, Jonquiere, Kénogami, Arvida, Bagotville and Port-Alfred now bas a population of over 110,000. The regional economy is based to a certain extent upon agriculture, with a specialisation in dairy farming. However, the principal emphasis is upon the aluminium and paper industries, which are supported by the great local hydro-electric power resources. The local economy is, however, dangerously subject to fluctuations of the international market.